Penerapan Model Pembelajaran Problem Based Learning Untuk Meningkatkan Keaktifan Belajar Siswa Pada Mata Pelajaran Ekonomi Kelas 11 IPS 2 SMA Negeri 2 Mendoyo - Sulasiawati, Ni Luh Astari; Indrayani, Luh (Jurnal Pendidikan Ekonomi Undiksha, 2023)
This research was conducted to find out the increase in student learning activeness by applying the problem based learning model. This type of study is classroom action research (CAR). This study involved teacher and student subjects with a total of 27 students consisting of 12 female and 15 male in class 11th  Social Studies 2 SMA Negeri 2 Mendoyo for the 2022/2023 academic year. The results of the study found that there was an increase in student learning activity seen from the data obtained after observing students during cycle I and cycle II. Cycle I the average value of students' learning activeness obtained by students was 52% in the less category. Cycle II the average value of student learning activity obtained by students was 82% which was in the very high category. Based on the results of the study, it can be concluded that the activeness of student learning using the problem-based learning model in economics subjects in class 11th Social Studies 2 SMA Negeri 2 Mendoyo has increased.